Associations of Gut Microbiota and Fatty Metabolism With Immune Thrombocytopenia - Yu, Xiaomin; Zheng, Qingyun; He, Yun; Yu, Dandan; Chang, Guolin; Chen, Cheng; Bi, Laixi; Lv, Jia; Zhao, Misheng; Lin, Xiangyang; Zhu, Liqing (Frontiers in medicine, 2022)
To determine whether gut microbiota, fatty metabolism and cytokines were associated with immune thrombocytopenia (ITP). In total, 29 preliminarily diagnosed ITP patients and 33 healthy volunteers were enrolled. Fecal bacterial were analyzed based on 16S rRNA sequencing. Plasma cytokines and motabolites were analyzed using flow cytometry and liquid chromatography-mass spectrometry (LC-MS), respectively. , , and were enriched at the genus level in ITP patients, while , , were depleted. At the phylum level, the relative abundance of and increased in ITP patients, while , , and the ratio decreased. Plasma levels of 5-hydroxyeicosatetraenoic acid (5-HETE), 6-trans-12-epi-leukotriene B4 (6t,12e-LTB ), and resolvin D2 (RvD ) were upregulated, and stachydrine, dowicide A, dodecanoylcarnitine were downregulated in ITP patients. Furthermore, RvD is positively correlated with order , 5-HETE is positively correlated with genus , and 6t,12e-LTB is positively correlated with genus . In addition, stachydrine is positively correlated with family , dowicide A is positively correlated with class , and dodecanoylcarnitine is positively correlated with order . Plasma levels of interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) were upregulated in ITP patients. Our study revealed a relationship between microbiota and fatty metabolism in ITP. Gut microbiota may participate in the pathogenesis of ITP through affecting cytokine secretion, interfering with fatty metabolism.